TEUMAKASIH BUKAN SEKADAR KATA: FILOSOFI UNGKAPAN ACEH SEBAGAI RESISTENSI BUDAYA GLOBAL - Muhammad Raihan (Yayasan An-Nur Meunara Baro, 2025)
The extinction of local languages has become a pressing global issue, as highlighted by UNESCO's alarming statistic that one regional language disappears every two weeks. Amid the tide of global linguistic homogenization, the Acehnese term teumakasih emerges as a subtle yet potent symbol of cultural resistance. This study aims to explore the revitalization of teumakasih in the context of glocalization, as well as its embedded semantic and identity values. A qualitative approach using linguistic ethnography and semiotic analysis was employed to trace the word’s usage in both physical spaces (coffee shops, prayer houses) and digital platforms (social media, marketplaces). Findings reveal that teumakasih is more than a polite expression; it carries a distinct local philosophy: teuma means